Vitamin D status and health‐related quality of life in patients with Type 2 diabetes. Issue 3 (3rd July 2015) - Krul‐Poel, Y. H. M.; Westra, S.; van Wijland, H. J. J.; Stam, F.; Lips, P.; Pouwer, F.; Simsek, S.
Abstract: Aims: To test whether vitamin D status was associated with health‐related quality of life in people with Type 2 diabetes mellitus. Methods: Demographic and clinical characteristics, including health‐related quality of life scores, were obtained from 241 adult patients with Type 2 diabetes managed with oral hypoglycaemic agents. Health‐related quality of life was assessed using the Short‐Form 36 Health Survey. Multiple logistic regression analysis was used to investigate the association between vitamin D status and health‐related quality of life, with adjustment for confounders. Results: The mean age of the patients included in the study was 67 ± 8 years. Their mean HbA1c concentration was 52 ± 8 mmol/mol (6.9 ± 0.7%) and their mean serum 25‐hydroxyvitamin D concentration was 59 ± 23 nmol/l. Vitamin D deficiency (serum 25‐hydroxyvitamin D < 50 nmol/l) was present in 38% of patients. No significant associations were found between vitamin D status and health‐related quality of life. Conclusions: Vitamin D status was not associated with health‐related quality of life in patients with Type 2 diabetes. This could be explained by the relatively high serum 25‐hydroxyvitamin D concentration, good glycaemic control and relatively good health‐related quality of life of all patients. A prospective study among patients with vitamin D deficiency and poor glycaemic control would be interesting for future research. What's new?: In observational studies vitamin D deficiency is associated with poor glycaemic control. Poor glycaemic control is associated with a reduced health‐related quality of life. No association between vitamin D status and health‐related quality of life was found in patients with well‐controlled Type 2 diabetes.